EVALUATION OF CLINICAL FEATURES, PARACLINICAL FINDINGS, AND TREATMENT OUTCOMES OF GIANT CELL TUMOR OF BONE - Thiên Đức, Nguyễn; Thành Toàn, Võ (Journal of Health and Aging, 2025)
To evaluate the clinical features, paraclinical findings, and treatment outcomes of giant cell tumor (GCT) of bone. Fifteen patients aged 20 to 40 years with bone lesions underwent surgery and histopathological examination and were diagnosed with “giant cell tumor of bone” between January 2011 and December 2024. There were 6 males and 9 females. The most common tumor location was the tibia (53.3%). The most frequent histological pattern was fibrosis, present in 11 cases (73.3%). The average follow-up duration was 55 months. Local recurrence occurred in 3 out of 15 cases, with no cases of metastasis. The GCT cases in our study shared pathological characteristics with classic GCT populations. No specific histological feature was associated with adverse outcomes. Curettage combined with bone cement filling proved to be an effective treatment option.